2001
DOI: 10.1086/318497
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Cidofovir in Papillomatosis

Abstract: An 8-year-old patient with severe recurrent respiratory papillomatosis and pulmonary spread was treated by systemic administration of cidofovir in association with laser treatment for tracheal lesions. Complete disappearance of the lesions in the pharynx and larynx and a significant yet incomplete regression in the bronchi and lung parenchyma were observed without deleterious side effects. This is the first case report of systemic use of cidofovir to treat recurrent respiratory papillomatosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 12 publications
0
24
0
Order By: Relevance
“…12) (167 (167,168) to conclude that intralesional injection of cidofovir may be of benefit in the treatment of severe respiratory papillomatosis in pediatric patients. From three case studies, it now appears that systemic (intravenous) cidofovir, whether combined with alpha interferon or used alone, would also be effective against recurrent respiratory papillomatosis with involvement of the lung parenchyma (11,58,221); under these conditions, laryngeal and tracheal lesions may regress or even disappear and pulmonary lesions may undergo consolidation.…”
Section: Downloaded Frommentioning
confidence: 99%
“…12) (167 (167,168) to conclude that intralesional injection of cidofovir may be of benefit in the treatment of severe respiratory papillomatosis in pediatric patients. From three case studies, it now appears that systemic (intravenous) cidofovir, whether combined with alpha interferon or used alone, would also be effective against recurrent respiratory papillomatosis with involvement of the lung parenchyma (11,58,221); under these conditions, laryngeal and tracheal lesions may regress or even disappear and pulmonary lesions may undergo consolidation.…”
Section: Downloaded Frommentioning
confidence: 99%
“…Armbruster et al reported a successful experience using a combination of intravenous cidofovir and IFN-α-2b in a 34-year-old woman with RRP and bilateral round areas of cavitation and consolidation (8). Van Valckenborgh et al reported the case of an 8-year-old girl who showed significant regression of lung lesions and no side effects after intravenous cidofovir therapy (9). De Bilderling reported one completely cured case of an 8-year-old girl, with suspected lung lesions of respiratory papillomatosis, who remained in remission for at least 2 years (10).…”
Section: Discussionmentioning
confidence: 99%
“…Cidofovir and interferon-a-2b in a 34-year-old woman with bilateral round cavitating consolidations due to recurrent respiratory papillomatosis. The only case report involving a child was an 8-year-old Chinese girl [Van Valckenborgh et al, 2001] who showed significant regression of lung lesions and no side effects after 23 doses of i.v. Cidofovir (5 mg/kg).…”
Section: Discussionmentioning
confidence: 99%
“…She was started on weekly injections of 5 mg/kg of i.v. Cidofovir (Vistide 1 ), according to the prescribed protocol [Van Valckenborgh et al, 2001]. Injections were preceded by 24 hr hyperhydration and associated with probenecid (25 mg/kg then 10 mg/kg/6 hr for 24 hr).…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation